Analisa Perlindungan Konsumen Pada Transaksi Pada Marketplace Blibli.com dalam Perspektif Hukum Islam Dan Hukum Positif - Zannati, Mifahul; Tedy Rahardi, Mohamad (Akademika : Jurnal Keagamaan dan Pendidikan, 2024)
This study analyzes the transaction of buying and selling through the Blibli.com Marketplace. Consumer protection at Blibli.com is not in accordance with the terms and conditions determined by Blibli.com. The research method used is a type of empirical legal research that is qualitative based on literature review (library research). The primary data source in this study was through interviews with Blibli.com marketplace users. The results of the study of consumer protection in transactions in the marketplace from the perspective of Islamic law and positive law, according to the perspective of Islamic law, there needs to be truth and accuracy of information when a business actor promotes their merchandise. An agreement is invalid if one party is in a forced state or also feels deceived, consumer rights are also protected in Islamic law and there are principles that are used as guidelines in conducting transactions in carrying out business activities. This is reinforced through the perspective of positive law in Law Number 8 of 1999 concerning Consumer Protection and the rights and obligations of consumers in articles 4 and 7 of the Consumer Protection Law. Business actors must be aware that consumers are protected by law